The Impact Of Financial Instruments Standard No. 9 Application On The Appropriateness Of Value To Accounting Information / An Applied Study On Private Banks Listed In The Damascus Stock Exchange / - ياسر كفا,; أوس جولاق , (Latakia University Journal - Economic and Legal Sciences Series, 2022)
The difference between Standard No. /39/ and Standard No. /9/ is in how losses (provisions) are calculated, where Standard No. 39/ recognizes realized losses only, while Standard No. /9/ uses a model for expected credit losses. The question is whether the users of the financial statements got what they needed by applying Standard No. /9/? Will the financial markets receive, after the inclusion of Standard No. /9/ and making it into force, better and more understandable information? In this study, the researcher verified whether the Financial Instruments Standard No. /9/ achieved the objective for which it was formulated for the financial markets and was able to increase the appropriateness of the value of the accounting information. This study relied on Ohlson's 1995 model to analyze the relationship between stock prices and accounting information (the book value of the stock represented in the statement of financial position, and the earnings per share represented in the income statement) so that the researcher can interpret the response of stock prices to that accounting information. The study period extended from 2011 until 2021, so that the study period is divided into the period before the application of the financial instruments standard No. /9/ of the year (2011-2017) and the period after the application of the standard from the year (2018-2020). The most important results are: - An increase in the explanatory power of earnings per share (EPS) approximately 54% after the application of Standard No. (9) - The increase in the explanatory power of the book value of the stock (EPS) approximately 11% after the application of Standard No. (9) - The value of the coefficient of determination increased from 90.00% to 94.5%, which indicates a rise in the explanatory power of accounting information (VPS, and EPS) approximately 4.5% after applying Standard No. (9)